The Role of Health Workers in Preventing Stunting in Children - Victor E D Palapessy; Rini Susanti; Nur Febrianti; Faridah Hariyani; Bambang Sucipto (Jurnal Ners, 2023)
The goal of this study was to find out what health workers can do to stop children from being too short for their age in villages. The method in this study is a qualitative research method with a type of literature study. The library research steps to be carried out in this study include: a) preparing equipment; b) compiling a work bibliography; c) managing time; d) reading and making research notes. In this study, data sources were obtained from relevant literature, such as books, journals, or scientific articles related to the selected topic. The data collection technique used in this library research is to find data about things or variables in the form of notes, books, papers or articles, journals, and so on. The research instrument used by researchers is a check-list list of research material classifications based on the focus of the study, writing schemes and maps, and research note formats. The data analysis technique used in content analysis research The results of this study show that the role of health workers in preventing stunting in the village has a very strategic role, in which these roles include: a. increasing awareness and education about the importance of balanced nutrition in children and families; b. identifying children who are at risk of experiencing stunting; c. providing a growth and nutrition monitoring program; d. providing appropriate nutritional supplements; and e. providing support and counseling for pregnant and lactating women. In addition, the role of health workers is to provide counseling on health and nutrition in the community, assist UKS in schools, and optimize community health centers (PUSKESMAS) by improving administration and providing medical equipment.